Exploring the Role of Experiential and Emotional Marketing in Building Customer Satisfaction and Loyalty in Coffee Shop - Rifqi Nur Fakhrurozi; Nyoman Indah Kusuma Dewi; Putu Adriani Prayustika; Ida Ayu Putri Widiasuari Riyasa (Binus Business Review, 2025)
The research explored the role of experiential and emotional marketing in enhancing customer satisfaction and loyalty within Bali’s competitive coffee shop industry. With the rapid growth of coffee shops in Bali, particularly Gen Z consumers who prioritized experiences and emotional connections, the research investigated how these marketing strategies influenced consumer behavior. Drawing on data from 183 customers of a prominent coffee shop in Denpasar, the researchers employed multilayer Partial Least Squares Structural Equation Modeling (PLSSEM) to analyze the relationships between experiential marketing, emotional marketing, customer satisfaction, and customer loyalty. The findings reveal that both experiential and emotional marketing have a significant positive impact on customer satisfaction. Furthermore, both experiential and emotional marketing also directly influence customer loyalty. Importantly, customer satisfaction ensures that consumers feel fulfilled with the value they receive, which in turn strengthens long-term loyalty toward the brand. These insights underscore the importance of creating immersive, emotionally resonant experiences that align with the values and lifestyles of modern consumers. For practitioners, the research recommends designing sensory-rich environments, fostering emotional brand connections, and leveraging storytelling to enhance customer retention. From an academic perspective, the research contributes to a deeper understanding of consumer behavior in experiential service industries, particularly in a tourism-driven market like Bali. Future studies should consider broader demographic samples and longitudinal designs further to explore the evolving dynamics of customer satisfaction and loyalty.